2021
DOI: 10.3390/educsci11100656
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Rubric Evaluation for Programming Education

Abstract: In evaluating the learning achievement of programming-thinking skills, the method of using a rubric that describes evaluation items and evaluation stages is widely employed. However, few studies have evaluated the reliability, validity, and consistency of the rubrics themselves. In this study, we introduced a statistical method for evaluating the characteristics of rubrics using the goal question metric (GQM) method. Furthermore, we proposed a method for measuring four evaluation results and characteristics ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Reliability refers to the consistency of scores given by different assessors or the same assessor on different occasions. If a rubric is reliable, it should produce similar results when used by different assessors to evaluate the same work or when used by the same assessor to evaluate the same work at different times [24,25]. One common method of assessing reliability is through inter-rater reliability, which refers to the degree of agreement between different raters or judges when scoring a given assessment.…”
Section: Rubric Validity and Reabilitymentioning
confidence: 99%
“…Reliability refers to the consistency of scores given by different assessors or the same assessor on different occasions. If a rubric is reliable, it should produce similar results when used by different assessors to evaluate the same work or when used by the same assessor to evaluate the same work at different times [24,25]. One common method of assessing reliability is through inter-rater reliability, which refers to the degree of agreement between different raters or judges when scoring a given assessment.…”
Section: Rubric Validity and Reabilitymentioning
confidence: 99%
“…In other studies, Saito et al. (2021) proposed the Goal Question Metric (GQM) method to evaluate the characteristics of a rubric to assess programing‐thinking skills, confirming the generality of these traits, and the consistency and the validity of the GQM method. Sánchez‐Ramírez et al.…”
Section: Introductionmentioning
confidence: 98%
“…The authors concluded that the rubric had a validity of content and construct, as well as reliability for the studied group. In other studies, Saito et al (2021) proposed the Goal Question Metric (GQM) method to evaluate the characteristics of a rubric to assess programing-thinking skills, confirming the generality of these traits, and the consistency and the validity of the GQM method. Sánchez-Ramírez et al ( 2022) designed and validated a rubric to evaluate competencies for employability.…”
Section: Introductionmentioning
confidence: 99%
“…Este método de evaluación requiere un diseño que puede llevar mucho tiempo, pero es el que presenta mejores resultados para conocer el estado actual de los estudiantes. Algunos trabajos presentados son: Cateté, Snider y Barnes (2016), Lakas y Belkacem (2021), Saito et al (2021), Wei, Saab y Admiraal (2021), en otros trabajos han usado rúbricas evaluativas (Mustapha et al, 2016), rúbricas basadas en realimentación (Allen y Tanner,…”
Section: Introductionunclassified